The relationship between psychological flexibility and health locus of control in patients after total hysterectomy: a latent class analysis - Liang, Wantian; Liang, Wenli; Ou, Danni (Frontiers in Psychology, 2025)
ObjectivesThis study aimed to examine the latent classes of psychological flexibility in patients after total hysterectomy and to analyze the characteristics of each class as well as their associations with health locus of control.MethodsA total of 214 hospitalized patients who underwent total hysterectomy at a tertiary maternal and child healthcare hospital in mainland China were surveyed between April 2022 and May 2023. Latent class analysis was conducted to identify distinct psychological flexibility classes. Logistic regression and one-way Analysis of Variance (ANOVA) were used to explore differences across classes in sociodemographic variables and health locus of control scores.ResultsThree latent classes of psychological flexibility were identified: Inflexible Class (n = 23, 10.75%), Moderate Class (n = 144, 67.29%), and Flexible Class (n = 47, 21.96%). Patients with children were significantly more likely to belong to the Moderate Class (OR = 18.920, p = 0.033); patients under age 45 were more likely to be in the Inflexible Class (OR = 0.028, p = 0.016); and those with a monthly per capita household income ≥ 5,000 CNY were more likely to fall into the Flexible Class (OR = 3.795, p = 0.027). Significant class differences were found in internal health locus of control (F = 5.649, p < 0.05) and chance health locus of control (F = 30.810, p < 0.05).ConclusionPsychological flexibility in patients after total hysterectomy shows heterogeneity. Healthcare providers should carefully assess the characteristics of each psychological classes and implement tailored interventions to support patients’ mental well-being and postoperative recovery.